Proceso de atención de enfermería en paciente con insuficiencia renal crónica: un estudio de caso - Arteaga Vallejo, Daniela Anais (2024)
Chronic kidney disease (CKD) is a progressive condition in which the kidneys gradually lose their ability to filter and remove waste and excess fluid from the body, potentially leading to the accumulation of toxins in the blood. A nursing care process was applied based on Marjory Gordon's model, which allowed for a comprehensive assessment through functional patterns to identify key alterations in fluid balance, renal function, and glucose levels. The interventions included continuous monitoring of hemodynamic status, precise administration of fluids and electrolytes. Education for the patient and their family about self-care and hygiene practices was also essential. The results showed a significant improvement in the patient's clinical stability, reflecting a positive response to the implemented care plan. Comprehensive care, focused on the patient and their family, proved crucial for recovery and health maintenance, with ongoing assessment and evidence-based interventions ensuring quality care and continuous improvement in the patient's health status.